The Influence of Training Methods on Improving Fundamental Techniques, Leg Power, and Coordination in Adolescent Volleyball: Literature Review - Hutauruk, Dela Oktavia; Lirazani, Devina; Ayumi, Najla Sari; Wirya, Nayla; Simamora, Andre William Pasoaran; Marpaung, Deni Rahman; Kurniawan, Randi (CV. Rayyan Dwi Bharata, 2025)
Inroduction: Mastery of fundamental techniques, leg power, and coordination is a crucialdeterminant of performance in adolescent volleyball athletes. However, many young athletesface limitations due to training methods that lack variation, do not match their developmentalcharacteristics, and do not properly emphasize comprehensive biomotor development. Theseissues often result in suboptimal improvement in their essential skills.Objective: This study aims to examine the influence of specific training methods on enhancingfundamental techniques, leg power, and coordination among youth volleyball athletes, as wellas to evaluate the effectiveness of each training method in supporting athletic performancedevelopment.Methods: An experimental design was used by implementing two types of training programs—agility hurdle and agility ring—to adolescent volleyball players over a structured trainingperiod. Measurement instruments included fundamental skills tests, leg power assessments,and coordination tests administered before (pre-test) and after (post-test) the intervention.Data were analyzed to determine changes in athletes’ abilities following the training.Results: The results indicate that both training methods significantly improved fundamentalvolleyball skills, particularly in passing, serving, and spiking. Notable enhancement in legpower was observed through increased jump performance and movement explosiveness.Coordination improvements were more pronounced in athletes with higher initial coordinationlevels, suggesting that baseline ability influences training outcomes.Conclusion: Structured, varied, and well-targeted training methods are effective in improvingfundamental skills, leg power, and coordination in adolescent volleyball athletes. Thesefindings highlight the importance of selecting appropriate training strategies as a foundation for designing more effective and sustainable athlete development programs.